FINISHING TEKNIK BATIK P ADA KERAJINAN KA YU DI SANGGAR KARY A MANUNGGAL - Martono, Martono; Suardana, Wayan; Hendri, Zulfi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
The object of this voucher program can publicity be reganded to de velop or enlarge batik technique finishing on wood craft. The more spesific objects ot this program are as follows: (1) To develop design of batik mo tives on wood craft, (2) To develop liquit wax application using electrical canting (drawing pen), (3) To develop color composed variation using "in digosol ang naptol", (4) To despose the wax using gazoline stove, and (5) Finishing wooden batik after drawing proces ti preserve the color from fungy using anti fungy Profan, using wood stain Mowilex, and Impra mela mine.The methode of research is to give idea of developing design form anbatik motives. To make design form and new motive design to give variative choices. Drawing proces using traditional canting and electrical canting. Coloring using painting technique and immersing for indigosol and immersing technique for "naptol" Wax disposing use fire ang gazoline stove. The last preserved finishing use wood stain Mowilex, melamine, and antifungy Profan.The result of this voucher program is 1) To develop new design; twoor three dimentional form. Two dimentional form is used in some ornaments such as "gunungan sekaten, baku! jamu (herb vendor), and mask. Three di mentionan form includes elephan model, bird model, horse model, cat model, and bridal model. 2) Motive design included some other varions mo tives besides batik motive alot of design choises. 3) Drawing proses uses traditional canting and electrical canting ( drawing pen) and electrical cant ing, is more smoth and flat because of the stable haet resolted more clean and healty. 4) Coloring using paiting technique and immersing technique for indigosol with composition 10 grams indigosol + 250 ml water + 1 tea spoon TRO for painting technique and 10 gram indigosol + 1 liter water + 1 tea spoon TRO for immersing rechnique. Material adapting color with com position 5 grams nitrit + 4 liter water + 50 ml HCL. Naptol color material compose of 50 grams naptol + 10 gram costic + 1 tea spoon TRO. Salt for color generate compose of 100 grams salt + 3 liter water . Disposing wax with composition of 1,5 kg soda abu + 20 liter water boiled using gazoline stove. The proces of the disposing wax using gazoline stove is more clean and healthy. The last plated after drawing/batik in order to preserve the 23 24 color using wood stain, melamine, ang using antifungy Profan . Understand ing the qualities and its estetic, there are some meaningful changes if we see it before and after the research. Key words: batik technique finishing, wood craft